The literary portrayals of Ivan Mazepa in Byron’s Mazeppa and Pushkin’s Poltava. A comparative analysis - Krol, Tatiana (Studia Rossica Posnaniensia, 2023)
This article provides a comparative analysis of Ivan Mazepa – the protagonist in the poems Mazeppa (1819) by George Gordon Byron and Poltava (1829) by Alexander Pushkin. It gives a brief outline of who Mazepa was to identify the reasons for this historical figure to have attracted the considerable attention of the Great Romantics. Deploying the theoretical method on recognition and the juxtaposition of differences of literary works within Reception theory developed by Mary N. Layoun, the article examines aspects of dissimilarity in the literary portrayals of the image of Mazepa in Byron’s and Pushkin’s poems. The juxtaposition of Mazeppa and Poltava explains ways in which details from Mazepa’s biography and exploits that inspired Byron’s creative imagination and kindled his desire to recount the story of Mazepa can be contrasted with Pushkin’s presentation of the same protagonist as generated by his own viewpoints on the political aspects surrounding the events of the Great Northern War, specifically the Battle of Poltava. The article applies Hans Robert Jauss’s concept of the horizon of expectations to examine the case of Pushkin’s reception of Byron. It argues that what underlies the nature of Pushkin’s disagreement with Byron is his emotional involvement with the subject matter.